Nankyoku ten - Amundsen, Roald; Nakada, Osamu (Dorufin Press, 1990)
Keywords: Antarktis; Fram (skip); ekspedisjoner; geografi; oppdagelsesreiser; polarområdene; sydpolen

Negtiationg a new regime: how CRAMRA came into existence - Andersen, Rolf Trolle (International Challenges, 1990)
Keywords: Antarktis; forvaltning; historie; mineraler; politikk

Protection of the environment in Antarctica: are present regimes sufficient? - Barnes, James N (International Challenges, 1990)
Keywords: Antarktis; forvaltning; miljøvern

Antarctica's cultural heritage: can ICOMOS help? - Barr, Susan (Icomos information, 1990)
Keywords: Antarktis; Sørishavet; historie; kulturminneforvaltning

The resource conventions implemented: the consequences for the sovereignty issue - Beck, Peter J (International Challenges, 1990)
Keywords: Antarktis; jus; politikk

The practical implications of the eco-system approach in CCAMLR - Beddington, John R; Basson, M; Gulland, J A (International Challenges, 1990)
Keywords: Sørishavet; forvaltning; økologi

Consultative status under the Antarctic Treaty: redefining the criteria? - Bos, Adrian (International Challenges, 1990)
Keywords: Antarktis; forvaltning; politikk

The design of CRAMRA: how appropriate for the protection of the environment? - Brown, Alan D (International Challenges, 1990)
Keywords: Antarktis; forvaltning; miljøvern; mineraler

Geological observations in Gjelsvikfjella and Mühling-Hofmannfjella - Bucher-Nurminen, Kurt; Ohta, Yoshihide; Austrheim, Håkon; Dallmann, Winfried K (Report of the Norwegian Antarctic Research Expedition 1989/90, 1990)
Keywords: Dronning Maud Land; NARE 1989/90; ekspedisjoner; forskning; geologi

Geology around the Norwegian Antarctic station "Troll", Jutulsessen, Dronning Maud Land - Dallmann, Winfried K; Austrheim, Håkon; Bucher-Nurminen, Kurt; Ohta, Yoshihide (Norsk Polarinstitutt, 1990)
During the Norwegian Antarctic Research Expedition 1989/90, a pennanent, unmanned research station was raised in Jutulsessen, Gjelsvikfjella, western Dronning Maud Land. The present report is a description of the geology of the area accessable from the station. Exposures of rocks in this part of Dronning Maud Land are restricted to a coastal mountain chain at c. 200-250 km distance from the ice shelf edge at elevations between 1000 and 3000 m. Quaternary deposits are particularly restricted to the inner parts of the Jutulsessen glaeier cirques. Deposits are till and talus which locally are admixing at slope angles of c. 25°. Moraines are poorly developed. Patterned ground ('stone pits') are common at slope angles below c. 15°. Recently active phenomena of special interest are ice-margin meltwater lakes with pingo-like 'blisters " the deep frost-shattering all over the mountain walls and hoIes in rock surfaces as a result of wind activity with grinding particles. The bedrock belongs to the East Antarctic craton. The area under consideration (western Miihlig-Hofmannfjella and Gjelsvikfjella) consists of high-grade metamorphic rocks and fonns one of the world's best exposed granulite terranes. Orthogneisses and minor metasediments have been intruded by a series of charnockites, partly altered to granulites (the 'Svarthamaren charnockite complex'), and a sequence of dyke rocks. Migmatization has affected large parts of the gneisses. Both gneisses and granulites/charnockites show abundant evidence of transition from granulite to amphibolite facies and vice versa, and the important role of fluid-rock interactions leading to these processes can be studied. The gneisses at Jutulsessen show a complex defonnation history. They are thought to be derived from granitic intrusions, though minor amounts of high-grade metamorphic, metapelitic gneisses may represent their original host rocks. Early tectonism (c. 1000-1200 m.y.) produced gneissosity, compositional banding and a leucosome phase under high-grade metamorphic conditions. This was followed by multiple and complex intrusive activity, partial migmatization and a tectonic overprint with abundant shear defonnation under amphibolite-facies conditions (c. 450-500 m.y.).
Keywords: Dronning Maud Land; NARE 1989/90; berggrunnsgeologi; geologi

The Antarctic in world politics - Dumas, Roland (International Challenges, 1990)
Keywords: Antarktis; politikk

Geodetic measurements in Dronning Maud Land - Eiken, Trond; Luktvasslimo, Brit Åse; Lytskjold, Bjørn (Report of the Norwegian Antarctic Research Expedition 1989/90, 1990)
Keywords: Dronning Maud Land; NARE 1989/90; ekspedisjoner; forskning; geodesi

Antarctica Treaty System: are there viable alternatives? - Falk, Richard (International Challenges, 1990)
Keywords: Antarktis; forvaltning; politikk

Observations of ice shelf water at the southern Weddel sea shelf break - Foldvik, Arne; Gammelsrød, Tor; Nordlund, Nina; Nytun, Kjell (Report of the Norwegian Antarctic Research Expedition 1989/90, 1990)
Keywords: NARE 1989/90; Sørishavet; Weddellhavet; ekspedisjoner; forskning; isshelf; oseanografi

The tides of the southern Weddell Sea - Foldvik, Arne; Middleton, Jason H; Foster, Theodore D (Deep Sea Research Part A. Oceanographic Research Papers, 1990)
Keywords: Sørishavet; Weddellhavet; isshelf; kontinentalsokkel; kontinentalsokler; tidevann

Marine biological studies in the Weddel sea and north of Dronning Maud Land - Gulliksen, Bjørn; Lønne, Ole Jørgen; Hellum, Cecilie (Report of the Norwegian Antarctic Research Expedition 1989/90, 1990)
Keywords: NARE 1989/90; Sørishavet; Weddellhavet; marin biologi

The ability of the Antarctic Treaty System to adapt to external challenges - Haron, Mohamed (International Challenges, 1990)
Keywords: Antarktis; forvaltning; politikk

The influence of the United Nations on the Antarctic system: a source of erosion or cohesion? - Harris, Stuart (International Challenges, 1990)
Keywords: Antarktis; forvaltning; politikk

Has CCAMLR worked? management policies and ecological needs - Heap, John A (International Challenges, 1990)
Keywords: Sørishavet; forvaltning; økologi

Microbial autotrophic and heterotrophic eucaryotes in Antarctic waters: relationships between biomass and chlorophyll, adenosine triphosphate and particulate organic carbon - Hewes, Christopher D.; Sakshaug, Egil; Reid, Freda M. H.; Holm-Hansen, Osmund (Marine Ecology Progress Series, 1990)
Microscopical examination of near-surface eucaryotic microbial populations in circumcontinental waters of Antarctica indicated that nanoplankton (<20 μm diameter) dominated in regions with low chlorophyll concentrations (< 1 μg l⁻¹). About 30 % of the mean nanoplankton carbon consisted of heterotrophic flagellates. Heterotrophic microplankton carbon (> 20 μm diameter) was generally less significant. The variation in phytoplankton biomass was the result primarily of changes in cell density of pennate diatoms in the East Wind Drift, and of centric diatoms in the Weddell Sea and the Scotia Ridge region. Autotrophic and heterotrophic carbon as determined by microscopical analysis were compared with data for total particulate carbon, chlorophyll a, and adenosine triphosphate. Estimates for the C:chl ratio of autotrophs increased with decreasing concentrations of chlorophyll a, with mean values of 46 in bloom waters and 144 in 'blue water'. A C:ATP ratio for heterotrophic nanoplankton was estimated to be about 100, while that for heterotrophic microplankton may be lower. Algorithms, incorporating concentrations of chlorophyll a and ATP, are described which allow estimates of autotrophic and heterotrophic microbial biomass.
Keywords: Sørishavet; alger; biomasse; fytoplankton; marin biologi; oseanografi; plankton; zooplankton

Høyest oppe, lengst borte: Mt. Vinson, 5200 m, høyeste fjell i Antarktis - Høibakk, Ralph (Polarboken, 1990)
Keywords: Antarktis; ekspedisjoner; fjellklatring

The pelagic distribution of marine birds in a heterogeneous environment - Hunt Jr, George L. (Polar Research, 1990)
Keywords: Antarktis; fugler; marin ornitologi; næring; polarområdene

The pelagic distribution of marine birds in a heterogeneous environment - Hunt Jr, George L (Polar Research, 1990)
Keywords: Antarktis; fugler; ornitologi; polarområdene; zoologi

I hjertet av Antarktis; Norge i Antarktis - Imbert, Bertrand C; Hem, Arne (Polarforskningens pionerer, 1990)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; Norge; Peter I. Øy; Roald Amundsen; Sydpolsekspedisjonen; Sørishavet; hvalfangst; oppdagelsesreiser

Antarctic science in a historical perspective: changing roles and functional development - Indreeide, Thor Vidar (International Challenges, 1990)
Keywords: Antarktis; forskning; historie; vitenskap

The legitimacy of the ATS - Jørgensen-Dahl, Arnfinn (International Challenges, 1990)
Keywords: Antarktis; jus; politikk

CRAMRA: the ugly duckling of the Antarctic Treaty System? - Joyner, Christopher C (International Challenges, 1990)
Keywords: Antarktis; forvaltning; miljøvern; mineraler

Radio-echo investigations in Dronning Maud Land - Kennett, Michael (Report of the Norwegian Antarctic Research Expedition 1989/90, 1990)
Keywords: Dronning Maud Land; NARE 1989/90; ekspedisjoner; forskning; geofysikk; isshelf; isstrøm; klimaendringer

CRAMRA and other enviromental regimes in the ATS: how well does CRAMRA fit? - Kimball, Lee A (International Challenges, 1990)
Keywords: Antarktis; forvaltning; jus; miljøvern

La oss arbeide! : A/S Laboremus gjennom 80 år 1910-1990 - Kolltveit, Bård ([A/S Laboremus], 1990)
Keywords: Norge; Sørishavet; hvalfangstindustri; hvalindustri; rederier; sjøfartshistorie

Virkninger av klimaendringer i polarområdene : bidrag til den interdepartementale klimautredningen - Kverndal, Arnt-Ivar; Elvebakk, Arve; Jaworowski, Zbygniew; Hansson, Rasmus (Norsk Polarinstitutt, 1990)
Keywords: Antarktis; biologi; drivhuseffekten; dyreliv; fiskeri; flora; havbruksnæring; havis; havnivå; isbreer; klimaendringer; klimagasser; permafrost; planter; polarområdene; vannressurser; økologi

Some Nitzschia and related diatom species from fast ice samples in the Arctic and Antarctic - Medlin, Linda K.; Hasle, Grethe Rytter (Polar Biology, 1990)
Some Nitzschia and closely related species have been examined in the light and electron microscopes from fast ice samples in the Arctic and Antarctic. Nitzschia neofrigida, forming arborescent colonies, and Nitzschia promare, forming loose ribbon colonies, are described as new species, both probably included in the distribution of other similar species. A new combination, Auricula compacta, represents the first report of this genus from ice samples. Colony formation is reported for the first time in Nitzschia arctica and Nitzschia taeniiformis. No biopolar species were found and several reports of Arctic species in Antarctic ice samples have been refuted.
Keywords: Antarktis; alger; biodiversitet; biologi; botanikk; diatomeer; fytoplankton; planteplankton; polarområdene

Towards firmer institutionalization of the ATS? Future role of the consultative meeting and the issue of a permanent secretariat - Messer, Kurt (International Challenges, 1990)
Keywords: Antarktis; forvaltning; jus

Medical contingency and biomedical research - Molvær, Otto Inge; Bendiksen, Fredrik S; Reitehaug, Per-Ivar (Report of the Norwegian Antarctic Research Expedition 1989/90, 1990)
Keywords: Dronning Maud Land; NARE 1989/90; biomedisin; medisin

Veien til CRAMRA: en studie av forhandlingene om opprettelsen av et mineralregime i Antarktis - Mørkved, Berit (Fridtjof Nansens institutt, 1990)
Keywords: Antarktis; forvaltning; mineraler; politikk

Report of the Norwegian Antarctic Research Expedition 1989/90 - Norsk, Polarinstitutt (Norsk Polarinstitutt, 1990)
Keywords: Antarktis; Dronning Maud Land; NARE 1989/90; Troll forskningsstasjon; Weddellhavet; geologi; marin økologi; meteorologi; zoologi

Geology of Gjelsvikfjella and western Mühlig-Hofmannfjella, Dronning Maud Land, east Antarctica - Ohta, Yoshihide; Tørudbakken, Bjørn; Shiraishi, Kazuyuki (Polar Research, 1990)
As a part of the Norwegian Antarctic Research Expedition 1984/85, geological mapping was performed in Gjelsvikfjella and western Muhlig-Hofmannfjella, Dronning Maud Land. The northern part of Gjelsvikfjella is dominated by the Jutulsessen metasupracrustals which have been intruded by a major gabbroic body and several generations of dykes. To the south the metasupracrustals gradually transform into the Risemedet migmatites. In western Muhlig-Hofmannfjella the bedrock is dominated by the large Svarthamaren Charnockite batholith. The batholith is bordered by the Snotoa metamorphic complex outcropping to the south and west in Muhlig-Hofmannfjella and it is characterized by a high content of partly assimilated country rock inclusions. Mineral paragenesis and geothermometry/geobarometry suggest a two-stage tectonothermal-igneous history with an initial intermediate pressure, upper amphibolite to granulite facies metamorphism followed by high temperature transformations related to the charnockite intrusion. The age of the initial tectonothermal event is probably about 1,100 Ma. Geochronological work in the present study (Rb/Sr whole rock) gave an age of 500 +/- 24 Ma for the Svarthamaren Charnockite, interpreted to record the age of crystallization. Late brittle faulting and undeformed dolerite dykes outcropping in Jutulsessen are believed to be related to Mesozoic crustal stretching in the Jutulstraumen-Pencksokket Rift Zone to the west.
Keywords: Dronning Maud Land; NARE 1984/85; geologi

Glaciologic and oceanographic studies on Fimbulisen during NARE 1989/90 - Orheim, Olav; Hagen, Jon Ove; Østerhus, Svein; Sætrang, Arne (Filchner-Ronne Ice Shelf Programme. Report, 1990)
Keywords: Dronning Maud Land; Sørishavet; ekspedisjoner; glasiologi; isbrem; oseanografi

Studies on, and underneath, the Ice Shelf Fimbulisen - Orheim, Olav; Hagen, Jon Ove; Østerhus, Svein; Sætrang, Arne (Report of the Norwegian Antarctic Research Expedition 1989/90, 1990)
Keywords: Dronning Maud Land; NARE 1989/90; ekspedisjoner; forskning; glasiologi; isshelf

Investigating Climate Change by Digital Analysis of Blue Ice Extent on Satellite Images of Antarctica - Orheim, Olav; Lucchitta, Baerbel (Annals of Glaciology, 1990)
Keywords: Dronning Maud Land; glasiologi; klimaendringer; satellitt; telemetri

lnvestigating climate change by digital analysis of satellite imagery of blue ice extent in Antarctica - Orheim, Olav; Luchitta, Baerbel (Annals of Glaciology, 1990)
Landsat-5 Thematic Mapper (TM) and SPOT data collected two years apart from an identical area of Dronning (Queen) Maud Land, Antarctica, have been analyzed to detect variations in surface features that may signal climatic change, and to establish a technique that readily identifies such changes. We found that selective principal component analysis (Chavez and Kwarteng 1989), on band ratios of near-IR/green, highlights changes in blue ice areas. The formation and preservation of blue ice is poorly understood, but we suggest that it generally takes longer to increase a blue ice area than to decrease it, and that blue ice extent is most sensitive to changes in accumulation rate. The investigated blue ice area shows a decrease in extent over the two-year period caused by incursion of snow that probably resulted from an increase in accumulation rate. Comparison of two TM images collected 18 days apart shows that transitory snow drifts have little effect on blue ice extent.
Keywords: Dronning Maud Land; glasiologi; klima

The implementation of CCAMLR: is the decision-making machinery conductive to good management? - Orrego Vicuña, Francisco (International Challenges, 1990)
Keywords: Sørishavet; forvaltning; miljøvern; politikk

Aspects of reproductive behaviour in a population of South Polar skua Catharacta maccormicki in Dronning Maud Land - Pedersen, Hans Christian (Report of the Norwegian Antarctic Research Expedition 1989/90, 1990)
Keywords: Dronning Maud Land; NARE 1989/90; ekspedisjoner; forskning; fugler; ornitologi; reproduksjon; zoologi

Petrology of Peter I Øy (Peter I Island), West Antarctica - Prestvik, Tore; Barnes, Calvin G; Sundvoll, Bjørn; Duncan, Robert A (Journal of volcanology and geothermal research, 1990)
Peter I Øy is located in the Bellinghausen Sea, 400 km NE of Thurston Island, West Antarctica. It is a Pleistocene volcanic island situated adjacent to a former tranform fault on the continental rise of the presently passive margin between the Pacific and Antarctica. New K-Ar age determinations ranging from 0.1 to 0.35 Ma show that the volcanism responsible for this island took place at the same time as post-subduction, rift-related volcanism occurred in the nearby Marie Byrd Land and the Antarctic Peninsula. The rocks of the island are alkalic basalt and hawaiite, benmoreite and trachyte. The basic tocks typically contain phenocrysts of olivine (Fo61–84), diopsidic augite, and plagioclase (ca. An60). Small xenoliths are present and consist of mantle-type spinel lherzolite, cumulate clinopyroxenite and gabbro and felsic inclusions that consist of medium-grained strained quartz, plagioclase, and abundant colorless glass. Chemically, the basic rocks are characterized by rather high MgO (7.8–10.2 wt.%) and TiO2 (3.1–3.7 wt.%) and relatively low CaO (8.4–9.5 wt.%) contents. They have steep REE patterns, [(La/Yb)N = 20] with HREE only 5 x chrondrite. Y and Sc are almost constant at relatively low levels. Compatible trace elements such as Ni and Cr show considerable variation (190–300 and 150–470 ppm, respectively.), whereas V shows only little variation. Sr and Nd isotope ratios vary slightly with 87Sr/86Sr averaging 0.70388 and 143Nd/144Nd 0.512782, both typical for ocean island volcanism. Lead isotope ratios are consistently high in basalts; 206Pb/204Pb = 19.194, 207Pb/204Pb = 15.728 and 208Pb/204Pb = 39.290, whereas benmoreïte is somewhat less radiogenic. Oxygen isotope analyses average ‰ . Incompatible trace elements vary by a factor of 1.5–2.0 within the range of the basic rocks. It is proposed that the incompatible trace-element variations represent different degrees (<10%) of partial melting, and that these melts were later modified by minor ( ‰ ) olivine and spinel fractionation. The very small variation in Y (and Sc) and the very fractionated REE pattern indicate that the source had an Y- and HREE-rich residual phase, most probably garnet. Furthermore, it is suggested that the source was slightly hydrous and that melting took place at 18–20 kbar. Trachyte was derived by multiphase fractionation of ne-normative basalts, and benmoreite from hy-normative parental liquids. The rocks of Peter I Øy are generally of the same type and age as those outcropping in extensional regimes on the nearby continent, and therefore, these occurrences may be related to each other in some way. However, the Peter I Øy rocks are considerably more radiogenic in strontium and less radiogenic in neodymium than the rocks of the Antarctic Peninsula and Marie Byrd Land. Possible explanations are that Peter I Øy represent asthenospheric hot spot activity, or transtensional rifting as subduction ceased.
Keywords: Peter I. Øy; geologi; petrologi

SCAR in the ATS: conflict or harmony? - Rinaldi, Carlos (International Challenges, 1990)
Keywords: Antarktis; forskning; forvaltning; politikk

Ingeniør Sæbjørnsens bukspretter - Ringstad, Jan Erik (Utkikksposten (Sandefjord) : kontaktorgan for Sandefjordmuseene, 1990)
Keywords: Nordmenn; Sørishavet; hvalfangst; hvalfangstindustri; hvalindustri; patenter; pelagisk; utstyr

Næringer i hvalfangstens grenseland - Ringstad, Jan Erik (Utkikksposten (Sandefjord) : kontaktorgan for Sandefjordmuseene, 1990)
Keywords: Christen Christensen; Sørishavet; historie; hvalfangst; hvalkokerier; hvalolje; næring; patenter; pelagisk; økonomi

Studies of breeding biology of Antarctic petrel and snow petrel in Mühlig-Hofmannfjella, Dronning Maud Land - Røv, Nils (Report of the Norwegian Antarctic Research Expedition 1989/90, 1990)
Keywords: Dronning Maud Land; NARE 1989/90; ekspedisjoner; forskning; fugler; ornitologi; zoologi

The relationship between the ATS and the LOS convention of 1982 - Safronchuk, Vasiliy S (International Challenges, 1990)
Keywords: Antarktis; Sørishavet; havrett; jus; politikk

Oxygen 18 and helium as tracers of ice shelf water and water/ice interaction in the Weddell Sea - Schlosser, Peter; Bayer, Reinhold; Foldvik, Arne; Gammelsrød, Tor; Rohardt, Gerd; Münnich, Karl Otto (Journal of Geophysical Research: Oceans, 1990)
Oxygen 18 and helium isotope data from stations located in the Filchner Depression, on the continental slope of the southern Weddell Sea, and in the central Weddell Sea are presented and discussed. The 18O and 4He signals imprinted on the water circulating under the Filchner/Ronne Ice Shelf (Ice Shelf Water, or ISW) due to melting of glacial ice at the base of the ice shelf are traced across the sill separating the Filchner Depression from the Weddell Sea. Low δ18O values are correlated with high 4He concentrations in the ISW found in the Filchner Depression (minimum δ18O values: −0.8‰; maximum 4He concentrations: about 4.7×10−8 cm3 STP g−1). The fraction of glacial meltwater contained in the ISW found in the Filchner Depression is estimated to about 6 to 7‰. The 18O and helium isotope data from the overflowing shelf water component observed on the continental slope confirm the hypothesis that ISW contributes significantly to the Weddell Sea Bottom Water (WSBW). On the basis of a inultiparameter water mass analysis it is discussed which fraction of the WSBW originates from ISW and which other shelf waters potentially could contribute to WSBW.
Keywords: Sørishavet; Weddellhavet; brehylle; geofysikk; hydrografi; isbrem; isshelf; oseanografi; smeltevann; vannmasser

Zwischen Kooperation und Konfrontation. Deutschland, Norwegen und die Walfangfrage in den 1930er Jahren - Scholl, Lars Ulrich (Sjøfartshistorisk årbok : Norwegian yearbook of maritime history, 1990)
Keywords: Norge; Sørishavet; Tyskland; historie; hvalfangere; hvalfangstindustri; hvalolje; pelagisk; samarbeid

Resource management and the changing profile of science in Antarctica: a growing pressure for relevance? - Scully, Richard Tucker (International Challenges, 1990)
Keywords: Antarktis; forskning; forvaltning

Marine geological studies in the Weddel sea - Sjøholm, Jorunn; Jansen, Eystein (Report of the Norwegian Antarctic Research Expedition 1989/90, 1990)
Keywords: NARE 1989/90; Sørishavet; Weddellhavet; ekspedisjoner; forskning; marin geologi

The relevance of the ATS as a model for international cooperation - Stokke, Olav Schram (International Challenges, 1990)
Keywords: Antarktis; jus; politikk

Ecophysiological adaptations in mites and collembolans in Dronning Maud Land - Strømme, Alexander (Report of the Norwegian Antarctic Research Expedition 1989/90, 1990)
Keywords: Dronning Maud Land; NARE 1989/90; ekspedisjoner; forskning; midder; miter; virvelløse dyr; zoologi; økofysiologi

Bibliographia Phytosociologica. Norwegian possessions in the polar regions - Sunding, Per (Excerpta botanica, Sectio B, 1990)
Keywords: Bouvetøya; Dronning Maud Land; Peter I. Øy; bibliografi; botanikk; polarområdene

Studies on the factors determining variation in the reproductive success of the Antarctic petrel Thalassoica antarctica in Svarthamaren, Mühlig-Hofmannfjella - Sæther, Bernt-Erik; Andersen, Reidar; Pedersen, Hans Christian (Report of the Norwegian Antarctic Research Expedition 1989/90, 1990)
Keywords: Dronning Maud Land; NARE 1989/90; ekspedisjoner; forskning; fugler; ornitologi; reproduksjon; zoologi

Frimerkespalten - Tandberg, Arne Ingar (Skipet, 1990)
Keywords: Antarktis; Bouvetøya; ekspedisjoner; filateli; historie; logistikk; skip

An Antarctic crossing as an analogue for long-term manned spaceflight - Ursin, Holger; Collet, Jérôme; Etienne, Jean L. (ESA Bulletin, 1990)
The long-duration space missions planned for the end of this century will involve both physiological and psychological problems for the crew who will fly them. If Europe is to achieve autonomy in space, it must increase its expertise in these associated disciplines. One means of acquiring relevant experience is to study human behaviour in environments that are similar from a psychological viewpoint. A planned crossing of the Antarctic by a six-man international team therefore offered ESA a unique opportunity to observe the psychological problems that can occur during an international expedition involving prolonged isolation in a hostile environment.
Keywords: Antarktis; fysiologi; psykologi

På hvalfangst med blyant og farvestifter - Wexelsen, Einar (Utkikksposten (Sandefjord) : kontaktorgan for Sandefjordmuseene, 1990)
Keywords: Nordmenn; Sørishavet; historie; hvalfangst; kunst; pelagisk

Pierce's kastebørse - et "Reodor Felgen" -patent med lang levetid - Wexelsen, Einar (Utkikksposten (Sandefjord) : kontaktorgan for Sandefjordmuseene, 1990)
Keywords: Sørishavet; historie; hvalfangst; hvalolje; patenter; pelagisk; utstyr

Glaciological and meteorological measurements in Dronning Maud Land - Winther, Jan-Gunnar (Report of the Norwegian Antarctic Research Expedition 1989/90, 1990)
Keywords: Dronning Maud Land; NARE 1989/90; ekspedisjoner; forskning; glasiologi; meteorologi

The unfinished task: CRAMRA and the question of liability - Wolfrum, Rüdiger (International Challenges, 1990)
Keywords: Antarktis; jus; mineraler